Conceptualizing a Privacy Framework for AI in the U.S. Consumer Tech Industry: Overcoming Legal and Regulatory Challenges - Faith Iziduh; Oluwatobi Opeyemi Adeyelu; Adeola Okesiji; Odunayo Oyasiji (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
The rapid advancement of artificial intelligence (AI) in the U.S. consumer tech industry has introduced significant privacy challenges that demand careful consideration and regulatory oversight. This paper proposes a conceptual privacy framework tailored to AI applications, aiming to address the unique legal and regulatory challenges posed by laws such as the California Consumer Privacy Act (CCPA), the Gramm-Leach-Bliley Act (GLBA), and the Health Insurance Portability and Accountability Act (HIPAA). The framework focuses on core principles such as transparency, accountability, and ethical governance, while integrating AI-driven solutions for compliance, including automated audits, secure data handling protocols, and user consent mechanisms. The proposed model strives to harmonize legal requirements with the innovation potential of AI technologies, ensuring that privacy is safeguarded without stifling technological progress. By providing a clear approach to AI compliance, the framework aims to enhance consumer trust, mitigate privacy risks for industry players, and offer regulators a more effective means of enforcement. Recommendations for future regulatory alignment, collaborative stakeholder engagement, and advancements in AI technology are also outlined to ensure the long-term success of the framework in this rapidly evolving landscape.